Let $\textbf{A}^\ast = -\textbf{A}$

Prove $\textbf{A}$ has only complex eigenvalues

Proof: Let $\lambda \in \mathbb{C}\ and\ \textbf{A}\vec{v} = \lambda\vec{v}\quad \vec{v} \neq \vec{0}$

$$\textbf{A}\vec{v} = \lambda\vec{v}$$ $$\Rightarrow (\textbf{A}\vec{v})^\ast = (\lambda\vec{v})^\ast$$ $$\Rightarrow (\vec{v}^\ast\textbf{A}^\ast)=(\lambda^\ast\vec{v}^\ast) $$ $$\because \vec{v} \neq \vec{0}$$ $$\therefore\vec{v}^\ast\textbf{A}^\ast\vec{v}=\lambda^\ast\vec{v}^\ast\vec{v}$$ $$\because \textbf{A}^\ast = -\textbf{A}$$ $$\therefore \vec{v}^\ast(-\textbf{A})\vec{v} = \lambda^\ast\vec{v}^\ast\vec{v}$$ $$\Rightarrow -\vec{v}^\ast\textbf{A}\vec{v} = \lambda^\ast\vec{v}^\ast\vec{v}$$ $$\because \textbf{A}\vec{v} = \lambda\vec{v}$$ $$\therefore -\vec{v}^\ast\lambda\vec{v}=\lambda^\ast\vec{v}^\ast\vec{v}$$ $$\Rightarrow -\lambda\vec{v}^\ast\vec{v}=\lambda^\ast\vec{v}^\ast\vec{v}$$ $$\Rightarrow \lambda\langle\vec{v}^\ast,\vec{v}^\ast \rangle=\lambda^\ast\langle\vec{v}^\ast,\vec{v}^\ast\rangle$$ $$\because \vec{v} \neq \vec{0}$$ $$\therefore \vec{v}^\ast \neq 0$$ $$\Rightarrow \langle\vec{v}^\ast,\vec{v}^\ast\rangle \gt 0\quad(\because \vec{v}^\ast\vec{v} = \langle\vec{v}^\ast, \vec{v}^\ast\rangle)$$ $$\Rightarrow -\lambda = \lambda^\ast$$ $$\Rightarrow \lambda \in\mathbb{R}$$

  • 1
    $\begingroup$ Side note: if $A$ is skew Hermitian, $iA$ is Hermitian. Assuming you have already shown that Hermitian matrices have real eigenvalues, this provides a shorter proof that $A$ has purely imaginary eigenvalues. $\endgroup$ – icurays1 Aug 9 '13 at 4:48
  • $\begingroup$ Here is the same problem. $\endgroup$ – Mhenni Benghorbal Aug 9 '13 at 19:29

First of all, I presume you mean to say $\mathbf A$ has only imaginary eigenvalues; what would an eigenvalue of a complex matrix be if not complex?

Second of all, you made the same mistake with the definition of an eigenvector that you did in your previous proof. Namely: $\vec v$ is an eigenvector if $\mathbf{\vec v}$ is non-zero and there is some $\lambda\in\mathbb C$ such that $\mathbf A \vec v = \lambda v$.

That is, we do not deduce $\vec v$ is non-zero from the nature of the matrix; it is supposed under the definition of an eigenvalue. We do not suppose that $\lambda \neq 0$ because for some eigenvectors, even with skew-Hermitian matrices, $\lambda$ can be zero. So, at the top of your proof, write

"Let $\vec v\neq 0$ and $\mathbf A \vec v=\lambda v$".

Instead. The rest seems fine.

EDIT: Also, note that $\vec v^*\vec v$ is a matrix of one entry, and so you should write

$\therefore \vec{v}^\ast \vec{v} \neq 0$

rather than

$\therefore \vec{v}^\ast \vec{v} \neq \vec{0}$

  • $\begingroup$ Note that there are different definitions of eigenvectors. For example I know one where Eigenvectors are vectors satisfying $Av=\lambda v$ and the Eigenvalues of $A$ are all $\lambda$ such that the Eigenspace is at least 1-dimensional $\endgroup$ – Dominic Michaelis Aug 9 '13 at 5:05
  • $\begingroup$ @DominicMichaelis thank you, I didn't realize that. $\endgroup$ – Omnomnomnom Aug 9 '13 at 5:34
  • $\begingroup$ thx to point out I'm missing the important definition of $\vec{v} \neq \vec{0}$ and $\lambda \in \mathbb{C}$ $\endgroup$ – bsdshell Aug 9 '13 at 6:48

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.